Dos territórios linhageiros aos regulados Coloniais no Vale do Lúrio e na circunscrição de Montepuez durante e após a Companhia do Niassa. Notas exploratórias para uma análise antropológica da cartografia - Medeiros, Eduardo (Africana Studia, 2020)
The use of scale maps of the region and the study of different eras is standard procedure in the field work of the ethnographer. In order to study the farming societies of northern Mozambique, like those of the Lurio River valley and the Montepuez region examined in this paper, a range of types of maps are essential: the physiographic, chorographic and geological, maps of soils and farming, and military maps. Furthermore, the comparative analysis of maps showing different points in history is necessary for understanding social spaces from a diachronic perspective; it provides a knowledge of the sociological understanding of cartographers in each historical era with regard to human spaces, their frontiers, channels of communication, trading routes, marketplaces, seats of chiefdoms, and so on. In general, almost all the old maps of this region are of note because they present a variety of relevant aspects, but there are gaps. This paper deals with the construction of social, cultural and political spaces over the long term.